Production of polysaccharide from Ganoderma neojaponicum imazeki / Nik Hafizah Nik Ubaidillah - Nik Hafizah , Nik Ubaidillah (2017)
Ganoderma species is the most popular medicinal mushroom for curing various diseases worldwide. Ganoderma neojaponicum (Imazeki), locally known as cendawan senduk was isolated from Bahau, Negeri Sembilan, Malaysia. This species has been used in natural healing and alternative medicine for external treatment of stomach ache in Malaysia. The most important therapeutic substance in Ganoderma spp. is polysaccharide. The aim of this study is to formulate low cost medium and optimize physical parameters for mycelial growth, β-glucan and total carbohydrate production from G. neojaponicum in shake flask and a 2-L stirred tank reactor (STR). Response surface methodology (RSM) was employed to obtain the best combinations of alternative carbon and nitrogen sources consisting of spent yeast (brewery industry) and brown sugar (sugar cane industry). Optimal growth medium requirements were 37.25 g/L spent yeast, 91.3 g/L brown sugar, 0.046 g/L Tween 80, with constant amount 0.5 g/L KH2PO4, 0.5 g/L K2HPO4 and 0.5 g/L MgSO4.7H20. The optimum physical parameters were temperature 26.72 oC, aeration 1.33 vvm, constant pH 6 and agitation 160 rpm. The optimal growth for G. neojaponicum was determined at 4 days of cultivation time with 25.32 g/L mycelial dry weight. The dried broth of G. neojaponicum showed higher total β-glucan 23.56±0.01% (w/v) and total carbohydrate 115.89±2.78 g/L compared to the dried mycelium. The mycelium and broth of G. neojaponicum were then partially purified for intracellular polysaccharide (IPS) and extracellular polysaccharides (EPS), respectively. The EPS of G. neojaponicum contained higher amount of total β-glucan and total carbohydrate compared to IPS, 9.41% (w/v) dan 80.81 g/L, respectively. The dried mycelium and broth as well as IPS and EPS were assessed for immunomodulatory property. The concentration 1000 μg/mL of IPS showed the most significant immunostimulating effect of human immune response in-vitro. The concentration enhanced up to 225% of proliferation activity of macrophage cell (RAW264.7), increased 460% phagocytosis activity and decreased 49.91% cytotoxicity effect of human colon cancer cell (HT29) compared to untreated cells (P<0.05). The G. neojaponicum mycelium and spent mycelium had significant (P<0.05) effect of Nf-kB inhibition of HT29. The dried mycelium of G. neojapocum was evaluated for its safety by acute oral toxicity test. The dried mycelium of G. neojapocum at a dose of up to 2000 mg/kg body weight/day did cause neither mortality nor toxic effects on the rats in 14 days.